The CEO is leaving : now what? : a three-phase process can help your organization navigate the boss's departure and transition smoothly into new leadership - Gillespie, David; Simpson, Tony (MIT Sloan Management Review, 2022)
Having a plan for managing the last 100 days before a CEO's departure is crucial in order to avoid organizational disruption. The authors share best practices for effectively managing CEO transitions, informed by the experiences of three senior leaders who recently left their organizations.